Optimization of Lead Placement in the Right Ventricle During Cardiac Resynchronization Therapy. A Simulation Study - Carpio, Edison F.; Gomez, Juan F.; Sebastian, Rafael; Lopez-Perez, Alejandro; Castellanos, Eduardo; Almendral, Jesus; Ferrero, Jose M.; Trenor, Beatriz (Frontiers in Physiology, 2019)
Patients suffering from heart failure (HF) and left bundle branch block (LBBB) show electrical and mechanical ventricular dyssynchrony causing an abnormal blood pumping. Cardiac resynchronization therapy (CRT) is recommended for these patients. Patients with positive therapy response normally present QRS shortening and an increased left ventricle (LV) ejection fraction. However, around one third do not respond favorably. Therefore, optimal location of pacing leads, timing delays between leads and/or choosing some related biomarker are crucial to achieve the best possible degree of ventricular synchrony during CRT application. In this study, we use a 3D electrophysiological computational model of the heart and torso to get insight into the changes in the activation patterns obtained when the heart is paced from different regions and for different atrioventricular and interventricular delays. The model represents a heart with LBBB and HF, and allows a detailed and accurate analysis of the electrical changes observed simultaneously in the myocardium and in the QRS complex computed in the precordial leads. Computational simulations were performed using a modified version of the O’Hara et al. action potential model, the most recent mathematical model developed for human ventricular electrophysiology. The optimal location for the pacing leads was determined by QRS maximal reduction. Additionally, the influence of Purkinje system (PS) on CRT response was assessed and correlation analysis between several parameters of the QRS was made. Simulation results showed that the RV upper septum near the outflow tract is an alternative location to the RV apical lead. Furthermore, LV endocardial pacing provided better results as compared to epicardial stimulation. Finally, the time to reach the 90% of the QRS area (t90QRSa) was a good predictor of the instant at which 90% of the ventricular tissue had been activated (t90). Thus, t90QRSa is suggested as an additional index to assess CRT effectiveness to improve biventricular synchrony.